Assessing Coagulation by Rotational Thromboelastometry (ROTEM) in Rivaroxaban-Anticoagulated Blood Using Hemostatic Agents. Issue 5 (19th June 2017) - Bar, Jonathan; David, Alexa; Khader, Tarek; Mulcare, Mary; Tedeschi, Christopher
Abstract: Introduction: The use of direct oral anticoagulants (DOACs) such as rivaroxaban (Xarelto) is increasingly common. However, therapies for reversing anticoagulation in the event of hemorrhage are limited. This study investigates the ability of hemostatic agents to improve the coagulation of rivaroxaban-anticoagulated blood, as measured by rotational thromboelastometry (ROTEM). Hypothesis/Problem: If a chitosan-based hemostatic agent (Celox), which works independently of the clotting cascade, is applied to rivaroxaban-anticoagulated blood, it should improve coagulation by decreasing clotting time (CT), decreasing clot formation time (CFT), and increasing maximum clot firmness (MCF). If a kaolin-based hemostatic agent (QuikClot Combat Gauze), which works primarily by augmenting the clotting cascade upstream of factor Xa (FXa), is applied to rivaroxaban-anticoagulated blood, it will not be effective at improving coagulation. Methods: Patients (age >18 years; non-pregnant) on rivaroxaban, presenting to the emergency department (ED) at two large, university-based medical centers, were recruited. Subjects (n=8) had blood drawn and analyzed using ROTEM with and without the presence of a kaolin-based and a chitosan-based hemostatic agent. The percentage of patients whose ROTEM parameters responded to the hemostatic agent and percent changes in coagulation parameters were calculated. Results: Data points analyzed included: CT, CFT, and MCF. Of the samples treated with a kaolin-based hemostatic agent, seven (87.5%) showed reductions in CT, eight (100.0%) showed reductions in CFT, and six (75.0%) showed increases in MCF. The average percent change in CT, CFT, and MCF for all patients was 32.5% (Standard Deviation [SD]: 286; Range:-75.3 to 740.7%); -66.0% (SD:14.4; Range: -91.4 to -44.1%); and 4.70% (SD: 6.10; Range: -4.8 to 15.1%), respectively. The corresponding median percent changes were -68.1%, -64.0%, and 5.2%. Of samples treated with a chitosan-based agent, six (75.0%) showed reductions in CT, three (37.5%) showed reductions in CFT, and five (62.5%) showed increases in MCF. The average percent changes for CT, CFT, and MCF for all patients were 165.0% (SD: 629; Range:-96.9 to 1718.5%); 139.0% (SD: 174; Range: -83.3 to 348.0%); and -8.38% (SD: 32.7; Range:-88.7 to 10.4%), respectively. The corresponding median percent changes were -53.7%, 141.8%, and 3.0%. Conclusions: Rotational thromboelastometry detects changes in coagulation parameters caused by hemostatics applied to rivaroxaban-anticoagulated blood. These changes trended in the direction towards improved coagulability, suggesting that kaolin-based and chitosan-based hemostatics may be effective at improving coagulation in these patients. J Bar, A David, T Khader, M Mulcare, C Tedeschi .Assessing coagulation by rotational thromboelastometry (ROTEM) in rivaroxaban-anticoagulated blood using hemostatic agents .Prehosp Disaster Med .2017 ;32 (5 ):580 –587 .